IMPACTS OF MAQSUD SHAYXZODA’S TRAGEDY “MIRZO ULUGBEK” ON THE DEVELOPMENT OF UZBEK LITERATURE AND ART - Jovliyev Javlonbek (European Journal of Humanities and Educational Advancements, 2022)
This article analyses Maqsud Shayxzoda’s tragedy “Mirzo Ulugbek” and his manuscripts. The spirit and the history of the nation are reflected in the literature. Both the past and the future live in the literature. So, its impossible to imagine the identity and the history of the continent without literature. World famous Uzbek and Azarbayjan poet, scientist, interpretor Maqsud Shayxzoda’s also connected the Centeral Asia with Luterature. As you study his manuscripts at the Alisher Navo’i State Literature Museum of the Academy of Sciences of Uzbekistan, you can see this